Non-isothermal kinetic study of de-oiled seeds cake of African star apple (Chrosophyllum albidum) using thermogravimetry. Issue 10 (October 2016) - Sokoto, M.A.; Singh, Rawel; Krishna, Bhavya B.; Kumar, Jitendra; Bhaskar, Thallada
Abstract: Thermal decomposition and kinetics behaviour of the de-oiled seed cake of African star apple ( Chrosophyllum albidum ) has been investigated using thermogravimetry under the nitrogen atmosphere from ambient temperature to 900 °C. The thermogravimetric data for the cake decomposition at six different heating rates (5, 10, 15, 20, 30 and 40 °C/min) were used to evaluate the kinetic decomposition of the cake using Friedman (FD), Kissinger-Akahira-Sunose (KAS) and Flynn-Wall-Ozawa (FWO) models. Thermal decomposition of the cake showed thermograms indicating dehydration and devolitilization stages (200–400 °C). The maximum temperature for the decomposition of the cake (Tmax ) increases from 289.42–335.96 °C with increase in heating rates. The average apparent activation energy (Ea) values of 153.15, 145.14 and 147.15 kJ/mol were calculated using Friedman, Kissinger-Akahira-Sunose, and Flynn-Wall-Ozawa models respectively. The extent of mass conversion (α) shows dependence on apparent activation Ea values which is an evidence of multi-step decomposition kinetic. The thermal profile and kinetic data obtained could be helpful in evaluating the thermal stability of the cake as well as modeling, designing and developing a thermo-chemical system for the conversion of the cake to fuel.